Study on KMnO4 and CH3COOK Properties in Microwave Chemical Reactors - Wang, Ping-Quan; Wang, Bo; Bai, Yang; Shu, Jun (Asian Journal of Chemistry, 2014)
In this paper, the changes of complex dielectric property of the potassium permanganate (KMnO4) and potassium acetate (CH3COOK) with different power are calculated and measured. The dielectric property of electrolyte solution with sylvine is studied. It is shown that the changes of real part of the complex permittivity are all small and the changes of the imaginary part of the complex permittivity of electrolyte solution are obvious. By analyzing the systems and variation error with different power, a conclusion is drawn that the measured results are credible and it is found that the imaginary part of K+ electrolyte solution permittivity is directly relative to power. What’s more, this method makes it possible to analyze the nonlinear time-dependent changing of reflection and absorption of microwave by the reactants and it is helpful for the design of microwave chemical reactors.